Implantation accuracy of custom-made acetabular components with iliac stem fixation for large bone defects in hip revision surgery - Nees, Timo A.; Hariri, Mustafa; Müller, Christian Thomas; Innmann, Moritz Maximilian; Spranz, David Maximilian; Westhauser, Fabian; Walker, Tilman; Reiner, Tobias (Orthopaedic surgery, 2025)
Objectives The treatment of extensive acetabular bone defects presents significant challenges in revision total hip arthroplasty (rTHA). Custom-made implants, tailored to patient-specific anatomy via 3D printing, offer potential advantages regarding implant stability and alignment. Precise positioning of these large-volume implants is crucial for primary stability and long-term fixation, but can be surgically demanding, especially when intramedullary iliac press-fit stems are used. In contrast to triflange custom-made implants, data on the implantation accuracy of custom-made acetabular components with iliac stem fixation remain limited. This study aimed to assess the accuracy of implant positioning by comparing preoperatively planned component positions with postoperative radiographic outcomes, focusing on anteversion (AV), inclination (INCL), and the center of rotation (CoR). Methods In this retrospective cohort study, 24 patients with large acetabular defects (Paprosky ≥ 3A) underwent rTHA with custom-made acetabular components with intramedullary press-fit iliac stem fixation between November 2022 and April 2024. Implantation accuracy was evaluated by comparing the planned positions on preoperative CT scans with the actual implant positions observed on 6-week postoperative radiographs using a previously validated methodology. Discrepancies in AV, INCL, and the CoR were analyzed. Results A high degree of alignment with preoperative plans was observed. The mean postoperative AV was 9.96° ± 6.4° (planned: 10.2°), and the mean INCL was 46.3° ± 3.2° (planned: 44.6°). The deviations were minor (Δ AV: −0.25°, Δ INCL: 1.7°), confirming the precision of implant placement. Four implants had CoR deviations exceeding 5 mm cranially (mean cranial shift: 1.77 ± 3.97 mm), and five exceeded 5 mm laterally. Most deviations were within clinically acceptable ranges. Conclusions Our findings demonstrate that custom-made acetabular components with iliac stem fixation can be implanted with high accuracy. Moreover, our results support the use of standard radiographs for the postoperative assessment of implant positioning precision. This study provides valuable insights into the accuracy of implant placement in complex rTHA cases, highlighting the role of patient-specific implant technologies in enhancing surgical outcomes.
Gesehen am 15.01.2026